Relationship between the amniotic fluid index at term and the perinatal outcome - Dobariya, Bhumika H.; Jani, Shree A.; Desai, Ajesh N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Amniotic fluid index (AFI) is commonly used to estimate amniotic fluid volume. A proper AFI is between 10 and 24 centimetres. If it is below 5 cm, it is can represent oligohydramnios, and in case AFI is above 24 cm, it can represent polyhydramnios. This study was undertaken to determine whether measuring AFI at term is useful in the prediction of perinatal outcome. Methods: A prospective study of 250 pregnant women with gestational age between 37 and 42 weeks was conducted at Sola Civil Hospital. AFI was measured in each patient using the Phelan’s technique and the perinatal outcome was studied. The results were analysed and presented in the form of tables and graphs. Results: Total 250 patients were studied. Out of them, 33 patients (13.2%) had AFI <=5, 215 (86%) had AFI between 6 and 24; and 2 patients (0.8%) had AFI >=25.19 out of 33 (57.57%) patients with AFI <= 5, had to undergo caesarean section, out of which, 12 caesarean sections (63.15%) were taken for non-reassuring foetal status. 36.27% (78/215) of patients with AFI between 6 and 24 underwent caesarean section, out of which 38.46% (30/78) underwent caesarean section for non-reassuring foetal status. Conclusions: In the presence of oligohydramnios, the rates of LSCS due to foetal distress, the occurrence of low Apgar score and of low birth weight are higher than in patients with normal liquor at term. Thus, measuring the amniotic fluid index at term can be helpful in the prediction of perinatal outcome.